2021
DOI: 10.47065/bits.v3i3.1139
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Metode Principal Component Analysis (PCA) Untuk Identifikasi Faktor-Faktor yang Mempengaruhi Sikap Mahasiswa Memilih Melanjutkan Studi ke Kota Malang

Abstract: The future of a nation depends on how good the quality of education and human resources of the nation is. Higher education is an important part of the world of education that carries the responsibility in an effort to educate the nation's life. This study aims to determine the factors that influence student attitudes in choosing to continue their studies at Islamic Higher Education (PTAI). The background of this research is that there is a significant gap between PTN and PTAI enthusiasts and the lack of studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…Pada penelitiannya mereka menggunakan metode untuk mereduksi 4 variabel yang berkorelasi menjadi 2 faktor baru yang tidak terdapat korelasi. Selain itu penelitian yang dilakukan oleh (Badri & Sari, 2021) dengan menggunakan metode yang sama yaitu Principal Compenent Analysis pada penelitiannya dalam penentuan faktor yang mempengaruhi sikap mahasiswa memilih program studi tadris matematika UIN Malang. Pada penelitiannya Badri menggunakan metode PCA untuk mereduksi 20 variabel yang berkorelasi menjadi 5 faktor yang mempengaruhi sikap mahasiswa memilih melanjutkan studi ke PTAI.…”
Section: Pembahasanunclassified
“…Pada penelitiannya mereka menggunakan metode untuk mereduksi 4 variabel yang berkorelasi menjadi 2 faktor baru yang tidak terdapat korelasi. Selain itu penelitian yang dilakukan oleh (Badri & Sari, 2021) dengan menggunakan metode yang sama yaitu Principal Compenent Analysis pada penelitiannya dalam penentuan faktor yang mempengaruhi sikap mahasiswa memilih program studi tadris matematika UIN Malang. Pada penelitiannya Badri menggunakan metode PCA untuk mereduksi 20 variabel yang berkorelasi menjadi 5 faktor yang mempengaruhi sikap mahasiswa memilih melanjutkan studi ke PTAI.…”
Section: Pembahasanunclassified
“…PCA can reduce data easily to simplify the observed variables by shrinking their dimensions. (Fenyvesi & Horváth, 2022) (Badri & Sari, 2021) (Wangge, 2021) This step is done to eliminate the correlation between variables by forming new sub-variables. CONCLUSION Based on the results of research using factor analysis using the PCA method, it is concluded that the tutor's performance assessment instrument has formed eleven main components with various sub-variables of each component such as seven sub-variables, three sub-variables, two sub-variables, and one sub-variable with a high correlation matrix value so that the tutor's performance assessment instrument can be declared to have a high level of validity and reliability so that it is appropriate to be used to assess the tutor's performance.…”
Section: Scree Plotmentioning
confidence: 99%